Design of Exponentially Weighted Median Filter Cascaded With Adaptive Median Filter - Nalli, Praveen Kumar; Kadali, Kalyan Sagar; Bhukya, Ramu; Palleswari, Y.T.R.; Siva, Asapu; Pragaspathy, S (Journal of physics. Conference series, 2021)
The objective of this paper is to design an II phase algorithm employing median filters for enlightening the performance in removing impulse noise during the processing of the image. The cascaded filter section employs an Adaptive median filter in the first phase followed by a Recursive weighted median filter (RWM) in the second phase. The RWM filter weight is selected with the Median Controlled Algorithm. As a design parameter, the exponential weights of RWM filters are used in the feedback path. The projected algorithm can achieve suggestively improved quality of image when compared to fixed weight or the Center Weighted Median filters.